Eyelid squamous cell carcinoma in xeroderma pigmentosa: A therapeutic challenge - Kaur, A; Agarawal, P; Jaiswal, V (Nepalese Journal of Ophthalmology, 2011)
A 10-year-old male, Muslim child diagnosed with xeroderma pigmentosa with a right upper lid malignancy presented as a therapeutic challenge because of the non-availability of normal facial skin for grafting and lid reconstruction. The lid lesion had been present for the last one month. The disease had been present for past five years with polymorphous, erythematous lesions all over the body. On examination, there was a hard reddish yellow mass in the lower lid with features of secondary infection along with corneal xerosis in both eyes. With a clinical diagnosis of malignancy, the lesion was subjected to a wide excision after the investigations. The resultant large tissue defect in the right lower lid region was managed by a full thickness trans-midline lateral forehead flap based on superficial temporal artery. Post operatively, there was a satisfactory graft uptake. The paucity of surgical options for the plastic reconstruction coupled with the large area to be reconstructed made our case worth reporting. Key words: erythematous; malignancy; forehead flap; excision DOI: 10.3126/nepjoph.v3i1.4285 Nepal J Ophthalmol 2011;3(5):86-87